Effects of a new compound probiotic on growth performance, antioxidant capacity, intestinal health, gut microbiota and metabolites of broilers - Meihong Zhang; Xin Li; Yuxuan Xiao; Runyi Cai; Xingliang Pan; Yongfei Hu (Poultry Science)
Compound probiotics have gained increasing recognition as feed additives for improving feed conversion ratio and intestinal health of broilers. Two Lactobacillus strains (Ligilactobacillus salivarius CML391 and Limosilactobacillus reuteri CML393) and two Bacillus strains (Bacillus velezensis CML396 and Bacillus paralicheniformis CML399) were isolated from broiler intestines and combined to form a new compound probiotic (referred to as “CML compound probiotic”). The effects of CML compound probiotic on broiler growth performance, antioxidant capacity, intestinal health, cecal microbiota, and microbial-derived metabolites were assessed in this study. A total of 120 male Arbor Acres chicks were randomly divided into two groups: a control group (CON) fed a basal diet and a CML group supplemented with the compound probiotic at 10⁹ CFU/kg of diet. Dietary supplementation with CML compound probiotic promoted broiler growth performance, enhanced antioxidant capacity, and improved intestinal health. Furthermore, the CML compound probiotic modulated the cecal microbiota by increasing beneficial bacteria such as Bacteroides, Phocea and Defluviitaleaceae UCG-011, and significantly elevated the concentrations of short-chain fatty acids (SCFAs). Metabolomic analysis revealed that the CML compound probiotic influenced lipid metabolism pathways, particularly glycerophospholipid and linoleic acid metabolism. In conclusion, this study indicated that the CML compound probiotic represents a valuable strategy for optimizing broiler growth performance and intestinal health.